Senescent Cell-Secreted Netrin-1 Modulates Aging-Related Disorders by Recruiting Sympathetic Fibers - Yu, Ai Qing; Wang, Jie; Zhou, Xiao Jia; Chen, Ke Yu; Cao, You De; Wang, Zhi Xiao; Mao, Ze Bin (Frontiers in Aging Neuroscience, 2020)
Cellular senescence is implicated in several lines of ageing-related disorders. However, the potential molecular mechanisms by which cellular senescence modulates age-related pathologies remain largely unexplored. Herein, we report that the density of sympathetic fibres (SFs) is significantly elevated in naturally aged mouse tissues and human colon adenoma tissues compared to the SFs densities in the corresponding young mouse tissues and human non-lesion colon tissues. A dorsal root ganglion (DRG)-human diploid fibroblast coculture assay revealed that senescent cells promote the outgrowth of SFs, indicating that the senescent cells induce recruitment of SFs in vitro. Additionally, subcutaneous transplantation of 2BS fibroblasts in nude mice shows that transplanted senescent 2BS fibroblasts promote SFs infiltration. Intra-articular senolytic molecular injection can reduce SFs density and inhibit SFs infiltration caused by senescent cells in osteoarthritis, suggesting senescent cells promote the infiltration of SFs in vivo in aged tissues. Notably, the elevated level of SFs contributes to impaired cognitive function in naturally aged mice, which can be reversed by treatment with propranolol hydrochloride, a non-selective β receptor blocker that inhibits sympathetic nerve activity (SNA) by blocking non-selective β receptors. Additionally, 6-hydroxydopamine (6-OHDA)-induced sympathectomy improved hepatic sympathetic overactivity mediated hepatic steatosis in high fat diet (HFD)-fed APOE knockout mice (APOE-/-mice) by reducing hepatic sympathetic nerve activity (SNA). Taken together, this study concludes that senescent cell-secreted netrin-1 mediated SFs outgrowth and infiltration, which contributes to ageing-related disorders, suggesting that clearing senescent cells or inhibiting SNA is a promising therapeutic strategy for improving sympathetic nervous system (SNS) hyperactivity-induced ageing-related pathologies.